PSIKOEDUKASI DAN PELATIHAN ASERTIF SEBAGAI UPAYA MENURUNKAN PERILAKU CYBERBULLYING SISWA - Lukman, S.N.; Aulani, S.D.; Kusumawardani, V.D.; Amora, V.B.; Agustina, L.S.S. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p05, 2024)
The existence of social media not only provides benefits but can also have negative impacts, such as the phenomenon of cyberbullying. Adolescents aged 10-18 years, as one of the largest age groups of social media users often struggle to manage their emotions effectively due to their developmental stage. They are prone to experiencing depression, anger, and have difficulty regulating their emotions. Furthermore, this can trigger the emergence of various problems, including cyberbullying. Some perpetrators may not even realize that their actions on social media is considered bullying. Cyberbullying involves individuals or groups deliberately attempting to hurt, threaten, insult, or degrade others. One preventive measure against cyberbullying is fostering individual assertiveness. It is essential to organize activities that provide knowledge and training for teenagers to refrain from engaging in cyberbullying. Psychological interventions, such as psychoeducation and assertiveness training, were provided to students at SMA X based on the results of initial interviews with counseling teachers and preliminary surveys with students. These community service activities are implemented to prevent individuals from becoming cyberbullying perpetrators and to reduce cyberbullying behavior among potential perpetrators. Keywords : assertive, cyberbullying, teenager